Analisis Tingkat Kesehatan Bank Dengan Menggunakan Metode Camel (Capital, Asset, Management, Earning, Liquidity) Pada PT. Bank Negara Indonesia (Persero) Tbk Tahun 2015 – 2017 - Manumpil, Gilbert; Taroreh, Henny S.; Keles, Dantje (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
The objective of the research is to evaluate the health level of PT. BankNegara Indonesia, Tbk from 2015 until 2017 by applying CAMEL method (Capital Adequacy Ratio, Asset Quality, Management of Risk, Earning Ability, and Liquidity Sufficiency).The object of this research is the financial report of PT. Bank Negara Indonesia, Tbk during three accounting periods form 2015 until 2017, which consists of balance, loss profit, capital, productive asset quality, earning ability, and liquidity reports. The results of the analysis show that capital, assets, management, earning, and liquidity of PT. Bank Negara Indonesia, Tbk are in a good position. The result of the position are showed in the following statements. It can be seen from the following data: the Capital Adequacy Ratio in 2015 was 25,7%; in 2016 was 18,4%; in 2017 was 18,3%. Asset quality which is based on Return on Asset (ROA), in 2015 was 2.45%, in 2016 was 1.89%, and in 2017 was 1.94%. The Management of Risk based on Net Profit Marjin (NPM), in 2015 was 37,1%, in 2016 was 32,5%, and in 2017 was 35,7%. The Earning ability is also based on the operational cost ratio to the operational ability (BOPO), in 2015 was 50,5%, in 2016 was 192,89%, and in 2017 was 181,31%. The Liquidity is based on Loan to Deposit Ratio (LDR), in 2015 was 6.54%, in 2016 was 7.74%, in 2017 was 3.93%. Even though there are increases and decreases in the result of the calculated ratios of CAMEL Pt. Bank Negara Indonesian is at first rank.